Effect of virtual reality exercise on interventions for patients with Alzheimer’s disease: A systematic review - Yi, Yali; Hu, Yuanyan; Cui, Mengxin; Wang, Cheng; Wang, Jibing (Frontiers in Psychiatry, 2022)
Virtual reality (VR) interventions are increasingly being used in rehabilitating and treating patients with neurological disorders. This study aimed to explore the effects of VR exercise interventions for patients with Alzheimer’s disease (AD). A systematic review of the published literature on randomized controlled trials of VR technology applied to patients with AD was conducted using the preferred reporting entry for systematic reviews and Meta-analysis guidelines. Descriptive analyses were performed to assess the quality of the studies in terms of the characteristics of the included studies, samples, diagnoses, types of VR technologies, subjective and objective levels of immersion, and quality of studies. Eight studies were included, including a pooled sample of 362 patients with AD. A systematic review showed that most studies focused on patients with AD’s cognitive and physical functions. The main finding was that VR interventions could help improve cognitive and physical balance in patients with AD. However, future studies should emphasize design and use well-accepted assessment tools to validate the effects of VR interventions further.